Istikhdām Aflām al-Rusūm al-Mutaharrikah Qanāt Youtube “Marhaban Academy” fī Ta’līm al-Lughah al-Arabiyah ladā Thullāb al-Saf al-Sābi’ bi al-Madrasah al-Sanawiyah - Nasution, Zulkifli Nasution; Zein, Achyar (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose- The purpose of this study is to find out the effectiveness of using the animated cartoon film YouTube channel "Marhaban Academy" and to find out the students' response in using the animated film YouTube channel "Marhaban Academy" as Arabic learning media for seventh grade students at MTs Yayasan Cerdas Murni Tembung. Design/Methodology/Approach- The method used in this research is descriptive qualitative research, data collected through observations, interviews, and questionnaires distributed to students, the subjects in this research are seventh grade students of MTs Yayasan Cerdas Murni Tembung with a total of 31 students who carry out teaching and learning activities using media animated cartoon film Youtube Channel "Marhaban Academy". The instrument used is a questionnaire for student responses using a Likert scale with five assessment criteria, namely Very Good (SB); Good (B); Enough (C); Less (K); and Very Less (SK).The purpose of this study is to find out the effectiveness of using the animated cartoon film YouTube channel "Marhaban Academy" and to find out the students' response in using the animated film YouTube channel "Marhaban Academy" as a medium for learning Arabic for class VII students at MTs Yayasan Cerdas Murni Tembung. Findings- Referring to the findings obtained in this study that the use of YouTube channel animated cartoon film "Marhaban Academy" in Arabic language learning shows that this media is an effective tool to increase students' interest, motivation, and understanding. Besides, students can build good cooperation ability among students, which is an important skill not only in academic context but also in daily life. This success confirms that learning with the creative media of "Marhaban Academy" YouTube channel animated cartoon film can support the development of students' social and collaborative skills effectively. Research Limitation/Implications- The problem limitation in this study is that it focuses on the effectiveness and student responses to the use of animated cartoon films on the YouTube channel "Marhaban Academy" in learning Arabic for seventh grade students at MTs Yayasan Cerdas Murni Tembung.